THE FEATURES OF TRAVELER WITH VACUUM AND SUCTION EQUIPMENT - Moroz, H. L.; Kuklev, M. O.; Tovt, B. M. (Science and Transport Progress, 2008)
The analysis of real mechanical system of the bridge crane with vacuum-sucker equipment is made and the design scheme for the mathematical model of dynamic processes created on the basis of the analysis is offered.